Subjective Well-being of Rural Dwellers in Russia: Factors and Their Significance - Saraykin, Valeriy; Nikulina, Yulia; Yanbukh, Renata (Journal of Economic Sociology, 2023)
The traditional policy of rural development in Russia has focused on bridging the gap between urban and rural areas by improving infrastructure and settlements in rural areas, but has not taken into account the perspectives and priorities of rural dwellers regarding their lives. Using data from The Russia Longitudinal Monitoring Survey from 2012 to 2019, this study seeks to understand rural residents’ priorities for rural development by analyzing their assessments of their own wellbeing and the factors that influence it. The study uses data discrimination form factor analysis to obtain multicomponent regressors; a logit model is constructed to determine the significance of selected factors. The study finds that factors such as health, education, person’s economic condition, and availability of utilities in the house have a significant positive impact on rural residents’ life satisfaction. However, the most dominant factor is “job satisfaction”, which includes the attitude of rural residents to (1) pay and working conditions and (2) opportunities for professional growth. The study also finds, unexpectedly, a nonlinear impact of economic condition on life satisfaction in rural areas, and a decrease in income returns. Additionally, the study identifies a group of rural residents who despite having minimal material goods, evaluate their lives as quite satisfactory. The study concludes by suggesting adjustments to the funding structure of the State Program “Integrated Rural Development” by increasing funding for measures to promote rural employment and expanding the focus to the non-agricultural sector of the rural economy.